Hyper-acute EEG alterations predict functional and morphological outcomes in thrombolysis-treated ischemic stroke: a wireless EEG study - Ajčević, Miloš; Furlanis, Giovanni; Naccarato, Marcello; Miladinović, Aleksandar; Buoite Stella, Alex; Caruso, Paola; Cillotto, Tommaso; Accardo, Agostino; Manganotti, Paolo (Medical & biological engineering & computing, 2021)
Owing to the large inter-subject variability, early post-stroke prognosis is challenging, and objective biomarkers that can provide further prognostic information are still needed. The relation between quantitative EEG parameters in pre-thrombolysis hyper-acute phase and outcomes has still to be investigated. Hence, possible correlations between early EEG biomarkers, measured on bedside wireless EEG, and short-term/long-term functional and morphological outcomes were investigated in thrombolysis-treated strokes. EEG with a wireless device was performed in 20 patients with hyper-acute (< 4.5 h from onset) anterior ischemic stroke before reperfusion treatment. The correlations between outcome parameters (i.e., 7-day/12-month National Institutes of Health Stroke Scale NIHSS, 12-month modified Rankin Scale mRS, final infarct volume) and the pre-treatment EEG parameters were studied. Relative delta power and alpha power, delta/alpha (DAR), and (delta+theta)/(alpha+beta) (DTABR) ratios significantly correlated with NIHSS 7-day (rho = 0.80, − 0.81, 0.76, 0.75, respectively) and NIHSS 12-month (0.73, − 0.78, 0.74, 0.73, respectively), as well as with final infarct volume (0.75, − 0.70, 0.78, 0.62, respectively). A good outcome in terms of mRS ≤ 2 at 12 months was associated with DAR parameter ( p = 0.008). The neurophysiological biomarkers obtained by non-invasive and portable technique as wireless EEG in the early pre-treatment phase may contribute as objective parameters to the short/long-term outcome prediction pivotal to better establish the treatment strategies. Graphical abstract Block diagram of study protocol and main findings. Assessment at admission including wireless EEG acquisition in emergency setting (< 4.5 from stroke onset), extracted EEG features before reperfusion thrombolytic treatment. The main findings in our study sample are summarized in two different exemplificative stroke patients with different pre-thrombolysis alterations of EEG parameters resulting in different final infarct volume extensions and short/long-term clinical outcomes (NIHSS, mRS).